Adherence to Healthy Lifestyle Recommendations in Brazilian Cancer Survivors - De Moraes-Ferrari, G (SPRINGER, 2023)
Purpose We aimed to describe the adherence to healthy lifestyle recommendations (regular consumption of fruits, vegetables, and salad greens; limit the consumption of red and processed meat, fast food, sugary and alcoholic beverages; keeping a healthy body weight, being physically activity, and not smoking) of 2314 cancer survivors and 86,517 adults without cancer diagnosis (general population) from the Brazilian National Health Survey, 2019. Methods We developed a score including eight healthy lifestyle recommendations proposed by the World Cancer Research Fund (i.e., the score ranged from 0 to 8; being 0 did not follow any recommendation and 8 followed all recommendations). Results Cancer survivors had higher healthy lifestyle score than the general population. In contrast, they presented similar adherence to the recommendations of physical activity, healthy body weight, and quitting smoking. Among cancer survivors, women (OR 1.52; 95%CI 1.12 to 2.06) and widows (OR 1.49; 95%CI 1.02 to 2.18) had greater odds of adherence to healthy lifestyle recommendations, adjusted for other sociodemographic characteristics. However, cancer survivors with complete primary education (OR 0.64; 95%CI 0.44 to 0.94) and higher education (OR 0.58; 95%CI 0.40 to 0.83) had lower adherence to the recommendations. Conclusion Our findings may be useful to support counseling and interventions aimed at promoting healthy lifestyles for Brazilian cancer survivors. Implications for Cancer Survivors Healthy lifestyle may reduce mortality and cancer recurrence, and improve quality of life in cancer survivors. Identifying factors associated with the adherence to healthy lifestyle in cancer survivors may be useful to support actions and interventions.